2007
DOI: 10.1007/s10493-007-9115-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of bifenazate and its principal active metabolite, diazene, to Tetranychus urticae and Panonychus citri and their relative toxicity to the predaceous mites, Phytoseiulus persimilis and Neoseiulus californicus

Abstract: Bifenazate is a novel carbazate acaricide discovered by Uniroyal Chemical (now Chemtura Corporation) for the control of phytophagous mites infesting agricultural and ornamental crops. Its acaricidal activity and that of its principal active metabolite, diazene, were characterized. Bifenazate and diazene had high toxicity and specificity both orally and topically to all life stages of Tetranychus urticae and Panonychus citri. Acute poisoning was observed with no temperature dependency. No cross-resistance was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 9 publications
2
44
1
1
Order By: Relevance
“…This suggests that additional factors might have been involved in the reported failure of the first propargite application in 2005 in San Joaquin Co., especially since the second application in the same year but at higher rate (Table 1) gave effective control. The LC 50 for bifenazate obtained in our test for the susceptible T. pacificus population is 30-90 times higher than LC 50 values reported for other susceptible tetranychids such as T. urticae and Panonychus ulmi in residual tests (Pree et al 2005;Van Leeuwen et al 2006;Ochiai et al 2007), suggesting that T. pacificus may be more tolerant. Two recent studies suggested that bifenazate acts as a Qo inhibitor, and cytochrome b, a protein encoded by the mitochondrial genome was proposed as its target-site (Van Leeuwen et al 2006.…”
Section: Discussioncontrasting
confidence: 67%
“…This suggests that additional factors might have been involved in the reported failure of the first propargite application in 2005 in San Joaquin Co., especially since the second application in the same year but at higher rate (Table 1) gave effective control. The LC 50 for bifenazate obtained in our test for the susceptible T. pacificus population is 30-90 times higher than LC 50 values reported for other susceptible tetranychids such as T. urticae and Panonychus ulmi in residual tests (Pree et al 2005;Van Leeuwen et al 2006;Ochiai et al 2007), suggesting that T. pacificus may be more tolerant. Two recent studies suggested that bifenazate acts as a Qo inhibitor, and cytochrome b, a protein encoded by the mitochondrial genome was proposed as its target-site (Van Leeuwen et al 2006.…”
Section: Discussioncontrasting
confidence: 67%
“…This indicates that these miticides are in fact compatible with this predatory mite. In another study, [22] found that exposure to bifenazate did not reduce fecundity, longevity, or prey consumption of adult female P. persimilis or N. californicus. Moreover, exposure to bifenazate, etoxazole, acequinocyl, and chlorfenapyr under laboratory conditions did not indirectly affect fecundity or reproduction of N. womersleyi females.…”
Section: Miticidesmentioning
confidence: 94%
“…Any indirect effects, which are sometimes referred to as sub-lethal, latent, or cumulative adverse effects may be associated with interfering with the physiology and behavior of natural enemies by inhibiting longevity, fecundity, reproduction (based on the number of progeny produced or eggs laid by females), development time, mobility, searching (foraging) and feeding behavior, predation and/or parasitism, prey consumption, emergence rates, and/or sex ratio [2, 13,16,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Bifenazate, a carbazate compound (Fig. 5) is highly effective against immatures and adults of spider mites, with rapid knockdown effect (Ochiai et al, 2007). Although it was first considered to be a neurotoxin, more recent experimental results indicate complex III as target site (van Nieuwenhuyse et al, 2009).…”
Section: New Synthetic Acaricidesmentioning
confidence: 99%